Motivasi Atlet Senam Ritmik Berprestasi Di Kota Semarang (Universitas Negeri Semarang, 2021)
The objectives of this study were (1) to find out the motivation factors of outstanding Rhythmic Gymnastics Athletes at the Wimilia Club of Semarang (2) to determine what facilities support the athlethes' motivation. This research employed quantitative method. Thirty-nine of 7-20 year-old athletes were the samples. The data analysis used descriptive frequency distribution. Questionnaires, interviews and documentation were used as the data collection techniques. The results showed the factors influencing the athletes’s motivation include internal and external factors. The internal factors are physiological needs (4.72) and self-actualization needs (4.47). External factors, security needs (4.65); social needs (4.23) and reward needs (4.69). The average internal factors is 4.6, while the external factors is 4.5. Based on the results, the internal factors affect the athletes' motivation. More, the facilities for the athletes are very good. The club provides professional trainer, decent equipment and adequate building. It is concluded that the motivation of the rhythmic gymnastics athletes comes from within (internal) and other factors that support the athlete's performance include good and adequate facilities.